Equine ovarian tissue xenografting: impacts of cooling, vitrification, and VEGF - Samara Silva Souza; Francisco Leo Nascimento Aguiar; Benner Geraldo Alves; Kele Amaral Alves; Fabiana Aparecida Santilli Brandão; Danielle Cristina Calado Brito; Ramon da Silva Raposo; Melba Oliveira Gastal; Ana Paula Ribeiro Rodrigues; José Ricardo Figueiredo; Dárcio Ítalo Alves Teixeira; Eduardo Leite Gastal (Bioscientifica, 2021)
Ovarian tissue transplantation methods using cooled and cryopreserved samples have been attractive options for fertility preservation in animal models and humans. The aim of this study was to evaluate the impact of previous exposure to cooling, cryopreservation, and VEGF on the overall efficiency of equine ovarian tissue after heterotopic xenotransplantation in mice. The endpoints evaluated were follicular morphology and development, follicular and stromal cell densities, angiogenesis (i.e. the density of new and mature blood vessels), collagen types I and III fiber densities, and total fibrosis. Ovaries of adult mares were harvested after ovariectomy, and ovarian fragments were xenografted in the i.p. wall of BALB nude mice. Ten types of treatments involving different combinations of cooling, cryopreservation, xenografting procedures, and VEGF exposure were compared. The novel aspect of this study was the use of equine ovarian tissue xenotransplantation in mice, challenging the fragments with different combinations of treatments. The main findings were (i) cooling but not cryopreservation was effective in preserving the follicular morphology, (ii) a greater percentage of developing follicles but lower follicular and stromal cell densities were observed after ovarian tissue engraftment, (iii) exposure to VEGF increased new and mature vessels in cryopreserved-transplanted tissue, and (iv) an appropriate balance in the collagen types I and III fiber ratio in cooling-transplanted tissue was observed after exposure to VEGF. This study contributes to advancing knowledge in the preservation of ovarian tissue after cooling-cryopreservation and transplantation aiming to be applied to genetically superior/valuable horses, livestock, endangered animals, and, possibly, humans.